An Investigation into Patient Non‐Attendance and Use of a Short‐Message Reminder System at a University Dental Clinic. Issue 1 (1st January 2016) - Storrs, Mark J.; Ramov, Helen M.; Lalloo, Ratilal
Abstract : Non‐attended appointments in health care facilities create inefficiencies and loss of clinical productivity: clinical teaching hours are reduced, impacting students' ability to meet the competencies necessary for professional registration. The aim of this study was to assess demographic and time‐related factors for patient non‐attendance at a dental school clinic in Australia. Appointment data were extracted from the patient management system for the years 2011 and 2012. Data included the status of appointment (attended, cancelled, or failed to attend [FTA]) and an array of demographic and time‐related factors. Multinomial logistic regression was conducted to assess relationships between these factors and appointment status. Attendance rates were also compared by year following implementation of a short message service (SMS) reminder at the beginning of 2012. The results showed that, of 58, 622 appointments booked with students during 2011 and 2012, 68% of patients attended, 23% cancelled, and 9% were FTA. The percentage of non‐attended (cancelled or FTA) appointments differed by demographic and time‐related factors. Females were 7% less likely to be FTA, those aged 16–24 years were five times more likely to be FTA, and early morning appointments were 18% less likely to be cancelled and FTA. With the SMS reminder system, the odds of a cancellation were 15% higher, but FTAs were 14% lower (both were statistically significant differences). This study found that failing to attend an appointment was significantly related to a number of factors. Clinical scheduling and reminder systems may need to take these factors into account to decrease the number of teaching hours lost due to patients' missing their appointments.